THE GREAT SCHOLARS OF IX-XII CENTURIES IN MOVARAUNNAHR AND KHURASAN. - Teshaboyeva Nafisa Zubaydulla qizi; Abdumalikova Sevinch Jasurbek qizi. (Ta'lim innovatsiyasi va integratsiyasi, 2024)
ANNOTATION:The article deals with the great scholars of the IX-XII centuries in Movarounnahr and Khurasan, highlighting their immense contributions to intellectual and scholarly pursuits during this period. These scholars, hailing from diverse fields such as philosophy, theology, mathematics, and astronomy, played a pivotal role in shaping the intellectual landscape of the Islamic world. Their works not only preserved knowledge from ancient civilizations but also laid the foundation for future developments in various disciplines. The enduring legacy of these scholars continues to inspire modern scholarship and serves as a testament to the vibrant intellectual heritage of Movarounnahr and Khurasan in the medieval era.